MONITORIZAREA ACTIVITĂŢII BIOELECTRICE A ENCEFALULUI LA STUDENŢI ÎN CADRUL ACTIVITĂŢII INTELECTUALE - Cojocari, Lidia (CEP USM, 2011)
Nature, duration and degree of brain bioelectrical reactivity during a tense intellectual activity (during the session,considered a emotional stress) as the control group and representatives of large individual differences and experimental aims depend on the functional reserves.
Keywords: activitatea bioelectrică a encefalului